Evaluation of Push-In/Integrated Therapy in a Collaborative Preschool for Children with Special Needs - Hernandez, Stephen J. (Journal of the American Academy of Special Education Professionals, 2012)
With support found in the literature for the utilization of push-in, or integrated therapy when providing speech language pathology, the use of a set of criteria for determining how therapy would be provided was evaluated in a preschool for children with special needs. Using a 5-item Likert scale, teachers and speech pathologists were surveyed regarding the criteria’s aide in determining how a student should be provided speech therapy. The collaboration that resulted from use of the criteria along with an assessment of the progress made by students receiving push-in services was also surveyed. Survey data indicated an affinity for the criteria, its facilitation of the collaborative process as well as the beneficial impact of push-in therapy on students’ development.